Initial Institutional Experience With Cryoablation Therapy for Breast Fibroadenomas: Technique, Molecular Science, and Post‐Therapy Imaging Follow‐up. (6th March 2019) - Sheth, Monica; Lodhi, Umairullah; Chen, Brandon; Park, Young; McElligott, Suzanne
Abstract : Cryoablation is a safe and effective nonsurgical treatment for breast fibroadenomas (FAs). The treatment response is inversely related to the tumor size, with lesions less than 2 cm showing an optimal response. Ultrasound (US) imaging follow‐up of the ablated tumor is recommended at 6‐month intervals for 2 years at our institution. Although a decrease in the size of the FA clinically and on US imaging is the expected treatment response, variations can be seen. Knowledge of typical US changes over time is imperative to prevent unnecessary rebiopsy or excision in patients who have undergone cryoablation. We will review the initial patient selection criteria, cryoablation technique, and US findings at regular follow‐up intervals after cryoablation of FAs through a series of cases treated at our institution.